2018
DOI: 10.4047/jap.2018.10.6.415
|View full text |Cite
|
Sign up to set email alerts
|

Screw loosening and changes in removal torque relative to abutment screw length in a dental implant with external abutment connection after oblique cyclic loading

Abstract: PURPOSEThis study investigated the effects of abutment screw lengths on screw loosening and removal torque in external connection implants after oblique cyclic loading.MATERIALS AND METHODSExternal connection implants were secured with abutment screws to straight abutments. The abutment-implant assemblies were classified into seven groups based on the abutment screw length, with each group consisting of five assemblies. A cyclic load of 300 N was applied at a 30° angle to the loading axis until one million cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…The intracortical fractures occurred in the trans cortex more frequently during the placement of the non-self-tapping screws [36] as compared with the self-tapping screws [5]. The position most commonly associated with the fractures were position no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracortical fractures occurred in the trans cortex more frequently during the placement of the non-self-tapping screws [36] as compared with the self-tapping screws [5]. The position most commonly associated with the fractures were position no.…”
Section: Resultsmentioning
confidence: 99%
“…The length of the NST and ST screws ranged between 18 and 24 mm in our study and all of the screws were placed bicortical. Previous research on a different length of the orthodontic implants (1.4–3.8 mm) did not show any significant correlation between the length of the implant and PRT as long as the implant was longer than 1.4 mm, which was considered as implants’ minimal length [36]. The minimal length of the cortical screw is considered when at least 3 threads of the implant can be placed through the far cortex in order to achieve the rigid fixation [1].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, orthopedic studies found it to be valuable to assess primary stability of locking hole inserts placed in locking plates subjected to cyclic loading as well as to evaluate and compare osseointegration of non‐self‐tapping and self‐tapping screws placed in a dynamic compression plate 18,19 . Another study on dental implants used PRT to evaluate the primary stability of various lengths of dental implants subjected to cyclic loading 27 . PRT measures the torque required to remove the implant from the tissue or orthopedic plate, thus indirectly assesses the stability of the screw and bone or screw and plate interface 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Of these two studies, the first one concluded that when a minimum length abutment screw was used (1.4 mm; 3.5 threads) there was hardly any difference in screw loosening post oblique cyclic loading compared with longer abutment screws. [ 10 ] The other study concluded that under thermal stress, there was no significant effect on torque when a minimum length screw was used (1.4 mm; 3.5 threads). [ 11 ]…”
Section: Factors Affecting Abutment Screw Looseningmentioning
confidence: 99%